2018
DOI: 10.1111/ddg.13594
|View full text |Cite
|
Sign up to set email alerts
|

Basic skin care in atopic dermatitis – new and established treatment options

Abstract: SummaryBasic skin care (basic therapy) is a mainstay in the treatment of atopic dermatitis, irrespective of disease severity and current disease activity. Consistent application of basic skin care plays a key role in restoring skin barrier function and reducing xerosis as well as pruritus. Moreover, it has been shown that concurrent basic therapy has steroid-sparing effects in acute disease flares. In long-term atopic dermatitis management, the use of basic skin care is associated with prolonged recurrence-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Considering that barrier dysfunction with epidermal water loss has an important relationship with AD, topical treatment using emollient is usually encouraged as a basic therapy [3,31,32]. Glatz et al in 2018 conducted an experiment in 6-month-old infants with family history of AD [33].…”
Section: Emollient Usementioning
confidence: 99%
“…Considering that barrier dysfunction with epidermal water loss has an important relationship with AD, topical treatment using emollient is usually encouraged as a basic therapy [3,31,32]. Glatz et al in 2018 conducted an experiment in 6-month-old infants with family history of AD [33].…”
Section: Emollient Usementioning
confidence: 99%
“…Several studies investigated the presence of ACD in patients with AD, with controversial results [10,12,13]. Given that recent studies have shown an immunological and barrier-compromising pre-activation of cells and cytokines even in unaffected skin of patients with atopic dermatitis [14,15], we chose a different, more refined approach: Atopic skin diathesis can be thoroughly assessed by the Erlangen Atopy Score (EAS) which was established and validated in the 1990s by Thomas Diepgen and colleagues [16,17]. This at least in Germany well-established and widely used score integrates 24 items to measure and calculate the probability of atopic skin diathesis (Table S1, online Supporting Information).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of AD follows a stepwise approach that is tailored according to disease severity and extension [85,97]. Patient's education and basic skin care must be carried out in all patients, including those without active skin lesions.…”
Section: Atopic Dermatitismentioning
confidence: 99%